Identification of Batoid Fishes from North Sumatra waters, Indonesia: Comparing between 12S and 16S rRNA gene as DNA marker - Khairiza Lubis; Mufti Sudibyo; Achmad Farajallah; Nisfa Hanim; Person Pesona Renta (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2021)
Indonesia is one of the biodiversity hotspot areas for chondrichthyan fishes in the world, including batoid fishes. Nevertheless, some of the biological information of batoid fishes in Indonesia are still limited, such as batoid’s gene sequences for molecular identification. Two of those DNA marker for identifying batoid species, that it’s information still lacking in Indonesia is 12S and 16S gene. Therefore, this study aimed to identify batoid fishes species from North Sumatra using 12S and 16S rRNA gene fragments and comparing the identification result of those two markers. The genomic DNA was extracted from the pectoral fin muscle of eight batoid samples from eight different species. Amplification of both gene fragments was done by using two pairs of primers which were manually designed. The amplicon from both genes was sequenced and then were analyzed. In the present study successfully obtained eight good sequences of each 12S and 16S rRNA gene fragment. Five batoid samples were successfully identified to species level using both of gene fragments due to these identification results were matched with our previous morphological identification results. The identification result of Rhinoptera javanica sample based on 12S rRNA gene fragment was inaccurate due to several reasons. One of the possible reasons was due to the gene region that this work used did not contain sufficient information to differentiate Rhinoptera javanica until species level. The 3 remaining samples were unsuccessfully identified to species level using both genes due to the lack of conspecific targeted gene reference sequences in the database.